Integrated LC-HRMS Metabolite Profiling and Multitarget Molecular Docking of Ginggiang (Leea aequata L.) Constituents Against Antidiabetic Targets - Purwaniati, Purwaniati; Susanti, Emy (Sciences of Pharmacy, 2026)
Type 2 diabetes mellitus (T2DM) is a metabolic disorder with complex pathophysiological pathways involving multiple physiological factors. Therefore, multitarget therapy has become one of the most rational therapeutic approaches for the management of T2DM. Ginggiang (Leea aequata L.) is a medicinal plant reported to contain various bioactive compounds with potential antidiabetic activity. This study aimed to explore the multitarget antidiabetic potential of the ethanolic extract of Ginggiang leaves through liquid chromatography–high-resolution mass spectrometry (LC-HRMS) analysis followed by molecular docking studies. LC-HRMS analysis was performed to identify compounds in the extract, while molecular docking studies were conducted to evaluate potential interactions between the identified compounds and multiple antidiabetic targets. The concentrated extract obtained by maceration using 96% ethanol was analyzed using LC-HRMS. The annotated compounds were subsequently used as test ligands in molecular docking studies. Molecular docking was performed using AutoDock 4.2.3 against α-glucosidase (PDB ID: 5NN8), SGLT2 transporter protein (PDB ID: 8HEZ), and DPP-4 enzyme (PDB ID: 5T4B). LC-HRMS analysis successfully annotated 31 compounds in the ethanolic extract of Ginggiang leaves. Molecular docking results suggested that catechin gallate and 2-amino-1,3,4-octadecanetriol exhibited favorable docking scores against all three target proteins and may be considered potential multitarget antidiabetic compounds. Several other compounds also showed favorable interactions with one or more targets. The results indicate that Ginggiang leaf ethanol extract may serve as a potential source of bioactive compounds for antidiabetic drug discovery. Nevertheless, further studies, including molecular dynamics simulations and experimental validation, are required to confirm these findings.